What is Wrong with Deductivism? - Bermejo-Luque, Lilian (Informal Logic, 2020)
In “Deductivism as an Interpretative Strategy: A Reply to Groarke’s Defense of Reconstructive Deductivism,” David Godden (2005) distinguished two notions of deductivism. On the one hand, as an interpretative thesis, deductivism is the view that all-natural language argumentation must be interpreted as being deductive. On the other hand, as an evaluative thesis, deductivism is the view that for a conclusion to follow, it has to follow of necessity from the premises—or, in other words, that being a good inference implies being deductive. The main goal of this paper is to show that evaluative deductivism is wrong.